2016
DOI: 10.7567/jjap.55.110306
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of magnetic properties and domain structures in Co/Ni multilayers

Abstract: Co/Ni multilayers with different layer thicknesses and repetition numbers were fabricated by magnetron sputtering. The films with appropriate Co and Ni layer thicknesses show strong perpendicular magnetic anisotropy. The results of magnetic force microscopy indicate that the films show a maze domain in the demagnetization state and that the domain width decreases with increasing layer thickness and repetition number. The magnetostatic and domain wall energies of the film stack were calculated on the basis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…The magnetization loops for Series A (figure 4(a)) show that the coercive field increases with increasing thickness. This in agreement with the results of Metaxas et al [9] on Pt/Co/Pt, but opposite to what Su et al [29] obtained for Co/Ni stacks, which suggests that this behavior is material-dependent. In addition, figure 4(b) demonstrates that DW velocity changes dramatically with the Co thickness: the DW velocity at 15 Oe is 2.5 × 10 −3 m s −1 for the d Co = 0.41 nm sample against 1.1 × 10 −7 m s −1 for the d Co = 0.52 nm sample.…”
Section: Domain Wall Velocity and Coercive Fieldsupporting
confidence: 87%
“…The magnetization loops for Series A (figure 4(a)) show that the coercive field increases with increasing thickness. This in agreement with the results of Metaxas et al [9] on Pt/Co/Pt, but opposite to what Su et al [29] obtained for Co/Ni stacks, which suggests that this behavior is material-dependent. In addition, figure 4(b) demonstrates that DW velocity changes dramatically with the Co thickness: the DW velocity at 15 Oe is 2.5 × 10 −3 m s −1 for the d Co = 0.41 nm sample against 1.1 × 10 −7 m s −1 for the d Co = 0.52 nm sample.…”
Section: Domain Wall Velocity and Coercive Fieldsupporting
confidence: 87%
“…Regarding Series B, it was shown that Co thickness is strongly determinant for both the coercive field and the DW velocity. In particular, the increase of the coercive field with the Co thickness is in agreement with the work from Metaxas et al 14 on Pt/Co/Pt, and opposite to what Su et al 24 obtained for Co/Ni stacks. Finally, we have assessed the changes in DW motion due to base pressure modification (Series C).…”
Section: Discussionsupporting
confidence: 91%
“…To clarify this point, we investigated the domain structure in the Pt 10/(Co 03/Ni 0.4) N /IrMn (t IrMn )/Pt 2 structure with different N, as shown in figure 4. By changing the repetition number N, the intrinsic domain structure can be tuned due to the variation of the dipole energy [27]. The first row in figure 4 show the MFM images of (Co/Ni) N /IrMn with t IrMn = 10 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Without considering the AFM layer, the domain size in the FM layer is determined by a balance of the dipolar energy and the domain wall energy, the former reduce domain size and the latter increase domain size. The balanced domain size is ~μm scale in (Co/Ni) N multilayers and increase with decreasing total thickness of FM layer or repetition number N [27]. Therefore, when an IrMn layer is deposited on the (Co/ Ni) N multilayers, a new balanced domain size was obtained to minimize the total energy in FM-AFM multilayer.…”
Section: Resultsmentioning
confidence: 99%